PL and ML characterization of Sr3EuxAl10-xSiO20 phosphor - Rangari, Varsha; Nayar, Vineet; Dhoble, S J (Recent Research in Science and Technology, 2012)
Sr3EuxAl10-xSiO20 phosphors were prepared by solid state diffusion method. The photoluminescence and mechnoluminescence properties have been studied. Prepared Sr3EuxAl10-xSiO20 phosphor shows the broad emission at 421nm due to 4f65d1ïƒ  4f7 of Eu2+ ion in the blue region of the spectrum. The excitation spectra of Sr3EuxAl10-xSiO20 phosphor shows at 356nm in the range of solid state lighting is useful for display devices. The ML activity of Sr3EuxAl10-xSiO20 (1 mole %) was determined for different impact velocities of piston and also for different masses of piston and results are discuss in this paper.